Staff-Group Consultation Within a Developmental Framework - Van Hesteren, Frank (Canadian Journal of Counselling and Psychotherapy, 2012)
In light of a perceived need to provide pre-service and practicing school counsellors with practical guidelines for functioning as consultants within a developmental framework, the writer: presents a nine-step in-service model suited to developmental consultation, describes a developmentally focused in-service workshop, and discusses how developmcntally oriented in-service work can be evaluated.